2007
DOI: 10.2146/ajhp050543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacist-led patient education on adherence to tuberculosis treatment

Abstract: Patients' adherence to TB treatment improved when a pharmacist provided patient education on medication use and addressed patients' pharmaceutical care issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 39 publications
2
102
0
9
Order By: Relevance
“…Child self-report includes 5-7, 8-12 and 13-18 years old. A 5-point Likert scale is utilized across the child self-report for ages [8][9][10][11][12][13][14][15][16][17][18] (0=never a problem; 1=almost never a problem; 2=sometimes a problem; 3= often a problem; 4=almost always a problem). Items were reverse-scored and linearly transformed to a 0-100 scale, so that higher scores indicate better health-related quality of life.…”
Section: Qol Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Child self-report includes 5-7, 8-12 and 13-18 years old. A 5-point Likert scale is utilized across the child self-report for ages [8][9][10][11][12][13][14][15][16][17][18] (0=never a problem; 1=almost never a problem; 2=sometimes a problem; 3= often a problem; 4=almost always a problem). Items were reverse-scored and linearly transformed to a 0-100 scale, so that higher scores indicate better health-related quality of life.…”
Section: Qol Measurementmentioning
confidence: 99%
“…There are few studies investigating the quality of life or adherence to therapy in this patient group. On the other hand, clinical trials have shown the benefits that pharmacist-led education can make to health outcomes and adherence in chronic illness [15,17]. However, to date no such study has been conducted in children with FMF.…”
Section: Introductionmentioning
confidence: 99%
“…105 The use of mobile phones for medication intake reminders and community-based networks/education, among others, are interesting initiatives in this sense. [106][107][108] Electronic medical information systems are becoming increasingly accessible, even in remote rural areas of lower resource countries. Cell phone networks are increasingly supporting data services that allow internet access.…”
Section: Role Of Care Delivery and Medical Information Systemsmentioning
confidence: 99%
“…For example, patients frequently cite the experience of TB medication side effects, as well as the perceived inability of HCWs to advise and manage these side effects, as a reason for non-adherence (13,14). Programs may consider creating positions for pharmacists within their teams, with roles in the teaching of patients, communities and staff, provision of consultative advice, program evaluation and research (15)(16)(17). In terms of behavioural and professional skills, the quality of the relationship between health care worker (nurse, doctor, community worker) and patient is central to promoting adherence to any health care intervention.…”
Section: Adherence To Tuberculosis Carementioning
confidence: 99%